DYNAMICS CONNECTION OF SOUNDSCAPE WITH ARCHITECTURAL ELEMENTS CASE STUDY: THE SEVEN SORROWS OF VIRGIN SAINT MARY CHURCH - Johnson (Jurnal Riset Arsitektur, 2019)
Abstract- Nowadays, spatial experience still plays important role in the making of the good quality of architectural spaces. The experience of the space is a multi-sensory experience, so architecture should emphasize its attention not only to visual experience but also other experience like auditory experience. The study was conducted to determine the dynamics connection of soundscape experience and The Seven Sorrows of Virgin Saint Mary Church, Pandu Street, Bandung.The research method is qualitative and descriptive analysis. The analysis is done through questionnaire distribution, field observation, analysis, and by relating it with the study of theories about church architecture, soundscape, sense of place, intention of architecture, and perception theory.In The Seven Sorrows Of Virgin Saint Mary Church are found quite a lot of source of noise which are considered as sounds that decline the quality of the people spatial experience. The noise sounds that are found there are the sound of airplane, motor vehicle, and many more. Those noises can disturb the praying activity. This indicates that there are some architectural elements that have not been able to work optimally. It can be the material, activity settings, building and site shape or character. Furthermore, relation between activity schedule and noises climax will be analized.Through design that concern in the multi-sensory aspects of experience, especially in auditory experience, the experience of space can be felt thoroughly and the quality of a public space can be increased. Key Words: Soundscape, Architectural Elements, Church, The Seven Sorrows of Virgin Saint Mary Church